2022
DOI: 10.3390/jcdd9090292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 on Arrhythmia

Abstract: The World Health Organization announced that COVID-19, with SARS-CoV-2 as its pathogen, had become a pandemic on 11 March 2020. Today, the global epidemic situation is still serious. With the development of research, cardiovascular injury in patients with COVID-19, such as arrhythmia, myocardial injury, and heart failure, is the second major symptom in addition to respiratory symptoms, and cardiovascular injury is related to the prognosis and mortality of patients. The incidence of arrhythmia in COVID-19 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 149 publications
0
33
0
1
Order By: Relevance
“…72 Proposed mechanisms of arrhythmogenesis are largely felt to be related to direct myocardial inflammation given the finding of greater degrees of troponin elevation in these patients as well as indirect effects from cytokine storm, hypoxia, and increased circulating angiotensin II resulting in a proinflammatory state (Figure ). 71,75,77,79,83,85 Similar to the trend seen in much of cardiovascular medicine at the onset of the pandemic, guidance on the management of patients living with preexisting electrical disturbances requiring ongoing electrophysiology care was put forth by the ACC/AHA/HRS in April of 2020. This guidance urged electrophysiology providers to avoid in-person visits, when possible, with a recommendation to perform device monitoring remotely as feasible.…”
Section: Arrhythmiamentioning
confidence: 99%
See 1 more Smart Citation
“…72 Proposed mechanisms of arrhythmogenesis are largely felt to be related to direct myocardial inflammation given the finding of greater degrees of troponin elevation in these patients as well as indirect effects from cytokine storm, hypoxia, and increased circulating angiotensin II resulting in a proinflammatory state (Figure ). 71,75,77,79,83,85 Similar to the trend seen in much of cardiovascular medicine at the onset of the pandemic, guidance on the management of patients living with preexisting electrical disturbances requiring ongoing electrophysiology care was put forth by the ACC/AHA/HRS in April of 2020. This guidance urged electrophysiology providers to avoid in-person visits, when possible, with a recommendation to perform device monitoring remotely as feasible.…”
Section: Arrhythmiamentioning
confidence: 99%
“… 72 Proposed mechanisms of arrhythmogenesis are largely felt to be related to direct myocardial inflammation given the finding of greater degrees of troponin elevation in these patients as well as indirect effects from cytokine storm, hypoxia, and increased circulating angiotensin II resulting in a proinflammatory state (Figure). 71 , 75 , 77 , 79 , 83 , 85 …”
Section: Arrhythmiamentioning
confidence: 99%
“…Several large studies have reported on persistent cardiac arrhythmias after SARS-CoV-2 infection [ 15 ]. The overall prevalence of cardiac arrhythmias ranges from 10 to 20% [ 16 ]. The numbers and rates indicated above and below may be different with regard to more recent SARS-CoV-2 variants and also vary country-specifically.…”
Section: Epidemiologymentioning
confidence: 99%
“…Pulmonary thromboembolism and pulmonary hypertension are well known reported complications of COVID-19 patients [ 20 , 21 ]. These clinical abnormalities provoke several pathological derangements ranging from accentuated intra-atrial pressures, elevated right ventricular afterload, increased myocardial oxygen demand, hypoxia, and massive atrial dilation all of which in combination increase the risk for developing atrial fibrillation [ 22 ] (Fig. 2 ).…”
Section: Main Textmentioning
confidence: 99%
“…1 ). The occurrence of electrolyte disturbances in COVID-19 patients is explained by acute renal failure, gastrointestinal disturbances, activation of renin angiotensin system and inflammation [ 22 ]. Hyponatremia and hypokalemia tend to induce atrial fibrillation via altering the electrophysiological properties of sino-atrial node (decreased beating rate) and pulmonary vein (attenuated burst firing) [ 28 ].…”
Section: Main Textmentioning
confidence: 99%